Impacts of AMI deployment in Thailand : generation expansion model - Pradsamon Rodchuea; Marpaung, Charles O.P.; Singh, Jai Govind; Weerakorn Ongsakul; PEA; Asian Institute of Technology Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
Emerging of Smart grid system in power industrial nowadays, the advanced metering infrastructure (AMI) becoming as the one of the most important technologies that Provincial. Electricity Authority of Thailand (PEA) plan to installing for the whole country. With its benefit to all stakeholders by providing the two way information which enable customers to manage their load. Firstly, the study aims to analyze the impacts of AMI on the power expansion planning in year 2011 to 2025 in the case of Thailand by developing generation expansion planning models by using Lindo programming. Then, the study purposes to analyze the GHG emission and abatement cost after AMI investment. The case which does not consider AMI is used as a base line of the study. Other 16 cases considering different estimated peak load reduction as the resulting in AMI implementation, each case study will be analyzed in different four customer participation rate of AMI installation. The results of the study reveals that with AMI installing, lower power generation and lower total cost of power generation would be reduced in every AMI case studies as well as the GHG emission. The power generation will be able to reduce from base case as 3,781,218.11 GWh to 3,689,404.18 GWh, as well as the total power plant cost that trends to decrease from the base case at 75,398.93 to 71,341.84 million dollars in the last case study. In addition, the results confirm that the CO2, CO, NOx emissions have a potential of emission reduction due to decreasing in amount of electric power from IPP during the studies period, whereas SO2 emission which is dominated by coal power generation technology showing slightly decrease in the last case study. At last, the CO2 abatement cost to avoid 1 ton of carbon emission shows the negative results in all scenarios. Therefore, it can claim that AMI deployment is the effective abatement strategy for CO2 reduction in Thailand.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Energy
Thesis (M.Sc.) - Asian Institute of Technology, 2012
Keywords: Greenhouse gas mitigation -- Thailand; Electric power systems -- Environmental aspects -- Planning -- Thailand